Multiculturalism in Shaping the Student Character of the Nation's Generation in the Era of Globalization Facing Challenges and Foreign Cultures - Nurul Hikmah; Jumiati; A. Octamaya Tenri Awaru (Formosa Journal of Applied Sciences, 2023)
Multiculturalism has become an ideology or way of life that respects ethnic, cultural, religious and racial diversity in facing the challenges of globalization and influencing the formation of student character as a nation's generation in this era. Applying the value of multiculturalism in everyday life can help students appreciate differences and tolerate other ethnicities, religions and cultures, as well as strengthen national identity. This article discusses the multiculturalism approach as a way of forming good student character to face foreign cultures and the challenges of the globalization era, as well as providing a positive view of the value of cultural and ethnic diversity in the Indonesian context.